European Stroke Organisation (ESO) standard operating procedure for the preparation and publishing of guidelines. (September 2021) - Steiner, T; Dichgans, M; Norrving, B; Aamodt, AH; Berge, E; Christensen, H; Fuentes, B; Khatri, P; Korompoki, E; Martí-Fabregas, J; Quinn, T; Toni, D; et al.
Abstract: The first European Stroke Organization (ESO) standard operating procedure (SOP) published in 2015 aimed at the implementation the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology to provide evidence-based guidelines for stroke management. This second ESO-SOP is aiming at further increase of the practicability of ESO guidelines and its technical implications. Authors comprised of the members of the ESO guideline Board and ESO Executive Committee. The final document was agreed on by several internal reviews. The second SOP comprises of the following aspects: rational for the SOP, the introduction of expert consensus statements, types of guideline documents, structures involved and detailed description of the guideline preparation process, handling of financial and intellectual conflicts of interest (CoI), involvement of ESO members in the guideline process, review process, authorship and publication policy, updating of guidelines, cooperation with other societies, and dealing with falsified data. This second SOP supersedes the first SOP published in 2015.